Archaeological theory - Johnson, Matthew, 1962- (Hoboken, NJ)
xvii, 372 sayfa
Keywords: “This book is an introductory essay on archaeological theory. It tries to explain something of what 'theory' is, its relationship to archaeological practice, how it has developed within archaeology over the last few decades, and how archaeological thought relates to theory in the human sciences and the intellectual world generally“ --